A universal model for grid-connected converters reflecting power-internal voltage characteristics - Peng, Qiao (2020)
With the still increasing penetration of renewable energy, the power system is being more power electronics based and digital. The diversity of grid-connected power converters with various control strategies complicates the analysis of system dynamics, when various and detailed converter models are adopted. This paper thus proposes a universal model of grid-connected converters that can reflect the essential power-internal voltage characteristics. With that, the diversity of converter outer controllers may be discarded, as their dynamics can be represented by the deviation of active and reactive power. In the proposed model, the transfer functions from the converter output power to the internal voltage and to the Phase-Locked Loop (PLL) output frequency are obtained, enabling the exploration of the stability of the internal voltage and the PLL performance. An example system is adopted to demonstrate the proposed model and simulated in PSCAD/EMTDC. The results show that the model is accurate to reflect the impact of controller parameters on the power-internal voltage stability of the entire system.